Aplikasi Pendukung Penetapan Harga Produk Untuk Usaha Mikro, Kecil, dan Menengah (UMKM) Berbasis Web Responsive - Rizki Wahyudi (STMIK Budi Darma, 2019)
This study aims to create a design for supporting pricing applications in Micro, Small and Medium Enterprises (MSMEs). Determination of product prices is an important thing, one of them from the aspect of costs so that products sold can provide benefits for the company. In pricing, companies must pay attention to production and nonproduction costs, in general, there are 4 main variables that must be included in the calculation of product prices namely Raw Material Costs, Labor Costs, Fixed Factory Overhead Costs and Variables, and Nonproduction Costs. In order for research to be directed, then the method of developing an Extreme Programming system is object-oriented, it can be done with a small team, and interactions that are intent- live with the user can maximize the development of an effective and efficient system. Stages of Extreme Programming, Planning, Design, Coding, and Testing. It is expected that with the pricing application the company can maximize profits through the price determination process. Based on the results of the Blackbox Testing test, all functional systems on the application work well.